Fabrication of a surface micromachined uncooled microbolometer based on the V2O5/V/V2O5 sandwich structure - Han, YH; Choi, IH; Son, CS; Kim, KT; Anh, NC; Shin, HJ; Moon, S (KOREAN PHYSICAL SOC, 2004)
A surface micromachined uncooled microbolometer based on the V2O5/V/V2O5 sandwich structure was designed and fabricated. A mixed vanadium-oxide phase was obtained by annealing the V2O5/V/V2O5 structure having an optimum layer thickness, and this method is very attractive for the reproducible deposition of the stable mixed vanadium-oxide phase. The multi-layer was deposited by using a conventional RF sputtering method, and the mixed vanadium oxide was formed by low temperature annealing at 300 degreesC. We designed the microbolometer with a pixel size of 70 x 70 mum(2) and a fill factor of about 50 % by considering such important factors as the thermal conductance, the temperature coefficient of resistance, device resistance, the infrared absorption, and thermal mass. Finally, we successfully fabricated the microbolometer by using surface micromachining technology, and we measured its bolometric properties.
Keywords: ARRAY